2020
DOI: 10.3390/cells9071566
|View full text |Cite
|
Sign up to set email alerts
|

miR-615 Fine-Tunes Growth and Development and Has a Role in Cancer and in Neural Repair

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that function as epigenetic modulators regulating almost any gene expression. Similarly, other noncoding RNAs, as well as epigenetic modifications, can regulate miRNAs. This reciprocal interaction forms a miRNA-epigenetic feedback loop, the deregulation of which affects physiological processes and contributes to a great diversity of diseases. In the present review, we focus on miR-615, a miRNA highly conserved across eutherian mammals. It is involved not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 94 publications
0
12
0
Order By: Relevance
“…Then, we found circRNA_100146 may be a target of miR-615-5p. Previously, many studies have reported miR-615-5p served as a tumor promoter in several tumors ( Guan et al, 2019 ; Godínez-Rubí and Ortuño-Sahagún, 2020 ). In PCa, miR-615-5p was shown to suppress the ability of proliferation and metastasis of tumor cells ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, we found circRNA_100146 may be a target of miR-615-5p. Previously, many studies have reported miR-615-5p served as a tumor promoter in several tumors ( Guan et al, 2019 ; Godínez-Rubí and Ortuño-Sahagún, 2020 ). In PCa, miR-615-5p was shown to suppress the ability of proliferation and metastasis of tumor cells ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are upstream mediators of a variety of molecular pathways due to their role in coordinating detailed biological mechanisms [128][129][130][131][132][133][134][135]. As occurs in different pathological events, miRNA dysregulation leads to alterations in normal cellular events [136,137]. Increasing evidence demonstrates that Nrf2 signaling is under surveillance of miRNAs in different pathological events for regulating response of cells to oxidative stress [138,139].…”
Section: Nrf2 Modulationmentioning
confidence: 99%
“…MiR-615-5p also participates in regulating cell growth, proliferation and migration, and has been shown to act as a tumour promoter or tumour suppressor, for example, through post transcriptional inhibition of oncogenes involved in essential biological processes, mainly by preventing invasiveness and metastasis, the main causes of tumour reappearance. 17…”
Section: Discussionmentioning
confidence: 99%